4(2x-5)=9(x-2)

Simple and best practice solution for 4(2x-5)=9(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-5)=9(x-2) equation:


Simplifying
4(2x + -5) = 9(x + -2)

Reorder the terms:
4(-5 + 2x) = 9(x + -2)
(-5 * 4 + 2x * 4) = 9(x + -2)
(-20 + 8x) = 9(x + -2)

Reorder the terms:
-20 + 8x = 9(-2 + x)
-20 + 8x = (-2 * 9 + x * 9)
-20 + 8x = (-18 + 9x)

Solving
-20 + 8x = -18 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-20 + 8x + -9x = -18 + 9x + -9x

Combine like terms: 8x + -9x = -1x
-20 + -1x = -18 + 9x + -9x

Combine like terms: 9x + -9x = 0
-20 + -1x = -18 + 0
-20 + -1x = -18

Add '20' to each side of the equation.
-20 + 20 + -1x = -18 + 20

Combine like terms: -20 + 20 = 0
0 + -1x = -18 + 20
-1x = -18 + 20

Combine like terms: -18 + 20 = 2
-1x = 2

Divide each side by '-1'.
x = -2

Simplifying
x = -2

See similar equations:

| Y-4=1/7(x-3) | | 9b^2+9b-40=0 | | -3.6x=51.48 | | w+20+6w+6+4w=180 | | (5+z)(5z-1)=0 | | 42+12=30 | | 13a+14+6a= | | 2cos^2-cosx=1 | | 5x^2+12x+10=x^2+10x | | (2e^-4)-((5/7)e^-7)=x | | -7-8b=17 | | 3a^2-33ab+54b^2= | | 0.2(5-3)= | | 4u^2-20u=0 | | 9m-27=4m+1 | | (2e^-4)-((5/7)e^-7) | | 4/5p–4=2/3p | | 144=-16x | | 21-6a=-2b+-8 | | t+2+t+28+3t=180 | | 3m-9=4m+1 | | 3x+2x+7+4x-20=180 | | 2x-6(-2x-4)=94 | | y/x=3/8 | | (2c+5d)3=x | | -2y+9=3 | | (2c-5d)3=x | | 3(x+5)-12=9+3x-6 | | graphY-9=0 | | 9*320=16*a | | Y+1=3(x-3) | | B+12=42 |

Equations solver categories